(untitled) (Bangladesh Agronomy Journal, 2023)
In modern agriculture, the application of nano fertilizers is increasing the productivity and stability of different crops by reducing the destructive effects of abiotic stresses. The nano particles are significant for their particle shape, potential reactivity, tunable pore size and high surface area. A pot experiment was conducted at the Department of Agronomy, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur during Rabi season (December 2020 to March 2021) to evaluate the effects of foliar spray of nano zinc (ZnO) in varying doses (0, 100 and 200 ppm) on growth, dry matter accumulation and yield of soybean under drought (40% of field capacity, FC) and control (80% of FC) conditions. The trial was conducted in a completely randomized design (CRD) with three replications. Plant height; fresh and dry weight of leaf, stem and whole plant; number of pods per plant; number of seeds pod-1; 100-seed weight and seed yield of soybean were suppressed due to drought stress. Under both drought and control conditions, the foliar application of nano zinc substantially improved the growth, dry matter accumulation and yield of soybean. In drought condition, the foliar spray of 200 ppm nano zinc solution increased plant height, total fresh and dry weight by 21.69, 34.23 and 76.03%, respectively. In drought conditions, nano Zn particles at 100 and 200 ppm increased seed yield by 26.79 and 63.50%, and in control conditions by 13.07 and 23.56%, respectively. As such the results indicated that foliar application of nano zinc oxide improved growth, yield and drought tolerance of soybean. Bangladesh Agron. J. 2022, 25(2): 73-82